Dampak Perubahan Iklim terhadap Produksi Pertanian dan Ketahanan Pangan Pedesaan - Budi Utomo; Rina Oktaviani (Primary Journal of Multidisciplinary Research, 2026)
Climate change is one of the global challenges that has significant impacts on various sectors, particularly the agricultural sector, which is highly dependent on climate and weather conditions. This study aims to analyze the impact of climate change on agricultural production and its implications for the food security of rural communities. Changes in rainfall patterns, increases in average temperatures, and the growing frequency of extreme weather events such as floods and droughts have disrupted agricultural production cycles in many regions. These conditions not only affect agricultural land productivity but also have consequences for farmers' incomes and the economic stability of rural households.The method employed in this study is a qualitative descriptive approach through a literature review of various scientific sources related to climate change, agricultural production, and food security. The findings indicate that climate change has led to a decline in crop yields of major commodities such as rice, maize, and vegetables due to increased pest and disease outbreaks as well as uncertainty in planting seasons. Furthermore, climate instability has disrupted the availability of irrigation water, which is essential for agricultural production processes, thereby increasing the risk of crop failure in several areas. From the perspective of food security, climate change has resulted in reduced local food availability, increased food prices, and limited access of rural communities to sufficient and nutritious food. This situation exacerbates the vulnerability of poor rural populations who heavily depend on agriculture as their primary source of livelihood. Therefore, effective adaptation and mitigation strategies are required, including the development of crop varieties resistant to extreme climate conditions, optimization of irrigation systems, and enhancement of farmers' capacities to cope with climate change. In conclusion, climate change has complex and significant impacts on agricultural production and rural food security. Collaborative efforts among governments, academics, and communities are essential to build a more resilient and sustainable agricultural system in the future.